Social Media and Elections in Southeast Asia: The Emergence of Subversive, Underground Campaigning. Issue 1 (2nd January 2021) - Tapsell, Ross
ABSTRACT: This article examines the use of social media platforms as a prominent form of election campaigning in three countries in Southeast Asia, namely Indonesia, Malaysia and the Philippines. Social media campaigning is now a prominent feature, not just in democratic election campaigns (Indonesia and the Philippines) but also in semi-authoritarian regimes (Malaysia). Through personal interviews with social media campaign professionals in all three countries, this research shows that social media is increasingly used to subvert mainstream media discourse and official channels of communication. This research examines the tactics of political campaigning on social media in a region with rapidly growing usage of such platforms, but where we see increasing signs of troubling election discourse online. As such, elections seemingly have two campaigns: one formal, mainstream media-driven discourse, and on social media platforms a different campaign that is subversive, underground and based around identity politics and disinformation.